Fluorescence enhancement through the formation of a single-layer two-dimensional supramolecular organic framework and its application in highly selective recognition of picric acid. Issue 48 (25th May 2016) - Zhang, Ying; Zhan, Tian-Guang; Zhou, Tian-You; Qi, Qiao-Yan; Xu, Xiao-Na; Zhao, Xin
Abstract : A novel two-dimensional (2D) supramolecular organic framework (SOF) has been assembled, which was further used as a fluorescent chemosensor to detect picric acid with high selectivity and sensitivity. Abstract : A two-dimensional (2D) supramolecular organic framework (SOF) has been constructed through the co-assembly of a triphenylamine-based building block and cucurbit[8]uril (CB[8]). Fluorescence turn-on of the non-emissive building block was observed upon the formation of the 2D SOF, which displayed highly selective and sensitive recognition of picric acid over a variety of nitroaromatics.